GEOCHEMICAL MIGRATION PROCESSES IN MOUNTAIN-VALLEY LANDSCAPES OF THE FERGHANA VALLEY AND THEIR IMPACT ON THE GEOECOLOGICAL ENVIRONMENT (Scientific journal of the Fergana State University, 2024)
The article shows the connections of paragenetic landscapes, their dependence on geological and geomorphological factors through geochemical migration processes. The role of landscape components in migration relations, their contrasting aspects, the participation of heavy metals in migration processes and their impact on the environment are assessed.